Developing Speaking English for Specific Purposes Materials for Broadcasting Major Students - The Case of Eleventh Grade of Vocational High School 1 Kendal - Suroyo, Suroyo; Faridi, Abdurrahman (Universitas Negeri Semarang, 2018)
Mastering speaking skill is a must for vocational school students in order to face the globalization era in this modern world. However, the speaking competences mastered by the vocational school students are mostly still low and need to be increased. That is why this research tried to answer some problems: (1) the lack of ESP speaking materials for students of vocational schools; (2) what kinds of ESP speaking materials the 11th graders of vocational schools needed; (3) how were the ESP vocational speaking materials developed; and (4) how effective was the developed materials. The researcher adopted some steps in educational research and development proposed by Borg and Gall in Vocational School 1 Kendal. The researcher chose one class of eleventh graders that had 32 students in it. In conducting the study, the researcher observed the existing materials and interviewed the teacher for the need analysis. After that, the researcher developed the ESP vocational speaking materials, then conducted the expert validation to some experts and tests and gave questionnaires to the students. The researcher, then, calculated the product’s effectiveness by using t-test. It was found out that the product was considered effective based on the t-test result and very good based on the questionnaire analysis. There were also some English speaking materials for vocational students, but unfortunately they were not in the form of ESP materials.